An Example of How to Die Nobly For Religion: The Influence of 4 Maccabees on Origen's Exhortatio ad Martyrium - DeSilva, David A. (Journal of early Christian studies, 2009)
In the course of his Exhortatio ad Martyrium, Origen retells the famous story of the martyrdoms of Eleazar, seven brothers, and the mother of the seven. While it is clear that he drew upon the version in 2 Maccabees from his verbatim recitations of the same, close study of his vocabulary, his supplements to the story, his choice of imagery, and his deployment of particular argumentative topics reveals the extent to which he drew upon 4 Maccabees, a text that would eventually be included in the codices of the Septuagint, as well. While the evidence is not sufficient to suggest that Origen included 4 Maccabees among the Scriptures, it is sufficient to demonstrate that he regarded it as a valuable resource for encouraging two Christian deacons to find the resolution to die for their religion, and to find such a death honorable and purposeful.